Mechanism of conduction in doped polyaniline - Campos, M.; Bello, B. (Iop Publishing Ltd, 1997)
The conductivity of H2SiF6-doped emeraldine polymers is studied as a function of temperature in the range 50 less than or equal to T less than or equal to 180 K. The dopant concentration of the samples varies between 0.1 M and 1.0 M. The temperature dependence of the do electrical conductivity gives evidence for a transport mechanism based on variable-range hopping in three dimensions. Using Mott's formula for the de conductivity, physically meaningful values of the density of states at the Fermi energy, the hopping energy and hopping distance are calculated.